Mechanical strain and bias-stress compensated, 6T-1C pixel circuit for flexible AMOLED displays. (November 2021) - Srivastava, Akriti; Dubey, Divya; Goswami, Manish; Kandpal, Kavindra
Abstract: This paper proposes a novel topology for a pixel circuit with a voltage-programmed threshold voltage compensation technique for amorphous indium gallium zinc oxide thin-film transistor (a-IGZO TFT) used in flexible AMOLED (Active-Matrix Organic Light-Emitting Diodes) displays. Simulation of the proposed circuit was done in Cadence Spectre using SPICE models for a-IGZO TFT, and the circuit utilizes six a-IGZO TFTs and one storage capacitor. Moreover, a detailed analytical analysis of the circuit is also done to estimate the error introduced during the emission phase. The simulation results showed that this pixel circuit offers excellent immunity to threshold voltage variation of driving TFT caused by bending and prolonged operation under gate bias. It can compensate for a wide range of VTH variations, i.e., 0 V–2.1 V, from the original 0.7 V of the TFT model, and the maximum percentage error in OLED current obtained was below 1.14%. The circuit proposed also alleviates the effect of electrical instability caused by threshold voltage shifts due to the compressive and tensile strain in the flexible substrate of the AMOLED display. The OLED current error was found to be below 0.0018% for a ±0.3% strain in the driving TFT. Graphical abstract: Image 1